Impact of Chemotherapy on Renal Parameters and Treatment Outcomes in Nasopharyngeal Carcinoma Patients: A Retrospective Study at Santa Elisabeth Hospital Batam - Friska Handayani; Frans Pahala Sinambela (International Journal on ObGyn and Health Sciences, 2023)
Nasopharyngeal carcinoma (NPC) poses a unique challenge, with distinct epidemiology and aggressive behavior. Chemotherapy plays a central role in NPC treatment, yet its impact on renal parameters remains a nuanced domain. This retrospective cohort study at Santa Elisabeth Hospital, Batam, delves into the dynamic interplay between chemotherapy and renal function in NPC patients. Electronic medical records of NPC patients undergoing chemotherapy were analyzed, focusing on urea levels, creatinine levels, and glomerular filtration rate (GFR). Statistical analyses, including paired t-tests and subgroup analyses based on chemotherapy regimens, were employed. Initial chemotherapy cycles induced a transient elevation in urea and creatinine levels, indicative of potential renal stress. Subsequent cycles revealed a trend toward stabilization or mild decline. GFR demonstrated a progressive but acceptable reduction, varying across chemotherapy regimens. Platinum-based regimens correlated with more pronounced alterations in urea and creatinine levels, while taxane-containing regimens exhibited a distinct impact on GFR. Patterns observed offer insights into personalized treatment approaches, guiding clinicians in optimizing therapeutic efficacy while safeguarding renal health. This research contributes not only to immediate patient care but also to the broader landscape of oncological knowledge, influencing future research agendas and evidence-based guidelines.